Late Antique and Early Medieval Cemetery in Novigrad. Preliminary Research Results (Archaeologia Adriatica, 2022)
Rescue archaeological excavations were conducted in the area of the former annex of the Stella Maris Hotel in Novigrad from late April to early June 2021. The excavations resulted in defining the area of spreading of the late antique and early medieval sub divo cemetery that surrounded the church of St Andrew north of the present-day parish church. The graves were damaged by soil tillage, and some time later, by the construction of a tourism-related building in the early 1960s. Several grave typologies have been determined. Burials in row graves are dominant. The graves are made of undressed limestone slabs, broken unevenly, of various sizes, laid one next to another, and stuck vertically in the earth. There are also burials in partially walled graves or simple laying out of the deceased on the bedrock. Remains of two late antique amphorae and numerous amphora sherds found in refuse pits suggest the earliest phase of burials. Position of the graves in the southern part of the excavated area was defined by drystone walls that were overlain by graves in the subsequent phase of burials. Graves are dated to the period from the early 5th to the 7th century in terms of typology of small finds dominated by coarse kitchenware and amphorae.
Keywords: Novigrad; rescue archaeological excavations; cemetery; Late Antiquity; Early Middle Ages